Epidemiology of malaria as it relates to utilization of insecticide treated nets among pregnant women and under five years children in South-South Nigeria - Odoko, Joseph O.; Nwose, Ezekiel U.; Nwajei, Samuel D.; Agege, Emmanuel A.; Moyegbone, John E.; Igumbor, Eunice O. (International Journal Of Community Medicine And Public Health, 2020)
Pregnant mothers and children under five years are exposed to malaria infection. One of the WHO recommendations on prevention of malaria is the use of insecticide treated nets (ITNs). The use of ITNs is still low in Nigeria. Is to access challenges and improvement on use of ITNs among pregnant mothers and care givers of children under five in Bayelsa, Delta and Rivers state respectively. Review of articles related to use of ITNs among pregnant mothers and under five years children were adopted using The American Journal of Human Genetics among 28 studies. Malaria is responsible for 30% childhood and 11% maternal mortality despite the availability on use of ITNs. ITNs were 62.8% effective in reducing febrile episodes and 84.1% effective in reducing marked levels of malaria parasitemia. Mass distribution of bed-nets has increase ownership of ITNs resulting to 81.5% in Nigeria. Free ITNs has resulted in universal household ownership but the use of the nets is still very low in Nigeria. Malaria interventions are threatened by pyrethroids used in all ITNs. Irritation and suffocation are challenges to utilization of ITNs. In health promotion on use of ITNs, manufacturers’ improvement on quality of ITNs is an epidemiological factor that could enhance the use among the vulnerable groups.